RETRACTED : The Influence of Democratic Leadership Style, Work Discipline, Intrinsic Motivation and Physical Work Environment on Employee Performance - Mohammad Febri Gunawan; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science)
This research aims to analyze the influence of democratic leadership style, work discipline, intrinsic motivation and physical work environment on the employees’ performance of PT. Straw Plus East Jakarta. This research data uses primary data in the form of a questionnaire to 100 respondents using the multiple linear regression method which was processed using SPSS 17.0 software. From data that has met the validity test, reliability test and classical assumption test. the variables are democratic leadership style, work discipline, intrinsic motivation and physical work environment on employee performance. From the model feasibility test, it shows that the four independent variables studied are proven to have a positive and real effect on the dependent variable together. Through testing the coefficient of determination (R2), it can be seen that democratic leadership style, work discipline, intrinsic motivation and physical work environment, each have an influence on employee performance, namely 93.9%, meaning that 93.9% of the dependent variable of employee performance can be explained by the independent variables are democratic leadership style, work discipline, intrinsic motivation and physical work environment. Meanwhile, the remaining 6.1% is explained by other variables that were not included in this research.